1999
DOI: 10.1017/s0043174500091827
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers indicate intraspecific variation in the control ofEchinochloaspp. with quinclorac

Abstract: Some species of the genusEchinochloaare troublesome weeds in rice fields. The taxonomy of this genus leads to confusion in many cases due to its great morphological diversity. Because of the differential sensitivity to the herbicide quinclorac shown byEchinochloaspp., it was necessary to assess the botanical and molecular characterization of this weed.Echinochloa colonum, E. oryzoides, andE. oryzicolawere very susceptible to quinclorac treatment; by contrast,E. crus-galliandE. hispidulashowed some degree of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 16 publications
(6 reference statements)
0
37
0
1
Order By: Relevance
“…The weed is a very aggressive invader, difficult to control, and causes major losses in rice production (Lopez-Martinez et al 1999). VanDevender et al (1997) reported that 20 BYG m Ϫ2 can reduce rice yield by 80%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The weed is a very aggressive invader, difficult to control, and causes major losses in rice production (Lopez-Martinez et al 1999). VanDevender et al (1997) reported that 20 BYG m Ϫ2 can reduce rice yield by 80%.…”
mentioning
confidence: 99%
“…In recent years, quinclorac has been used to control BYG, but some of these populations also have developed increased tolerance to quinclorac (Lopez-Martinez et al 1999). The development of these herbicide-resistance populations has led to increased interest in alternative methods to control BYG (Gealy et al 2003).…”
mentioning
confidence: 99%
“…Although high values of genetic variation are sometimes reported, this appears to be typical of plants that reproduce mainly by seed (Asins et al 1999;Lopez-Martinez et al 1999;Roy et al 2000;Rutledge et al 2000). For genetic polymorphism, seven primers produced a total of 55 RAPD bands, about 85.1% of which were polymorphic among the 34 populations of E. crus-galli.…”
Section: Discussionmentioning
confidence: 98%
“…E. crus-galli found in rice production exhibits significant differences in morphology and genes, which may be related to different sensitivity to herbicides. Because of this high variability, morphological characters and physiological response to herbicides in different taxonomic classifications have been proposed by several authors who found different results by using morphological, isozyme or molecular markers (Asins et al 1999;Lopez-Martinez et al 1999;Rutledge et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1977). This weed is a very aggressive invader, difficult to control, and causes major losses in rice production (Lopez‐Martinez et al . 1999).…”
Section: Introductionmentioning
confidence: 99%